80.0k views
2 votes
-2x + 4y = -4
x - 3y = 6

1 Answer

3 votes

Answer:

(-6, -4)

Explanation:

Let's eliminate x using the addition / subtraction method:

-2x + 4y = -4

x - 3y = 6

becomes

-2x + 4y = -4

2x - 6y = 12

-------------------

-2y = 8

Dividing both sides by -2, we get y = -4.

Substituting -4 into the 2nd original equation results in:

x - 3(-4) = 6, or x + 12 = 6, or x = -6

The solution of this system of linear equations is therefore (-6, -4).

User Alexander Burov
by
4.7k points